Investigating the effects of alkalization on mechanical properties of enset fibers using digital image correlation technique - Abebayehu Abdela; Bart Buffel; Belete Sirahbizu; Frederik Desplentere (Results in Engineering)
The characterization of fiber level tensile properties is vital for conducting micromechanical analyses and developing mechanical models of materials and their composites. This characterization is significantly influenced by the precision of diameter estimations, as the load applied is derived from the measurements obtained from the testing machine. In this regard, the diameter found using microscopy denotes the external diameter which is larger than the diameter pertaining to actual load-carrying cross-section. This research introduces a novel method for calculating diameter by taking into account the lignocellulose structure and hydrophilicity of the fiber. This method is needed to allow a more precise representation of tensile properties in both untreated and treated fibers. The determination of the diameter associated with a structural load-bearing cross-sectional area involves establishing the connection between density, mass, and volume subsequent to the determination of density through Helium Pycnometry. The experiment design was framed and analyzed using Python programming, Minitab V21 and JMP 13. The measured density of Enset is 1.38 g/cm3. The tensile strength of the fiber using digital correlation techniques test revealed that 69.44 %, of the fibers attains strength of 500–1000 MPa and 25 % showed a strength of 800–900MPa. The vital role in treated fibers is attributed to the concentration of sodium hydroxide, with the duration of immersion also being a critical factor. Therefore, lignocellulosic structure of Enset fiber must be considered when evaluating its tensile strength. Moreover, chemical treatments can improve the fiber's surface properties, indicating a potential for enhanced performance at the composite level.